EFFECTS OF THE CLIMATE GRADIENT ONF THE WOOD DENSITY OF Cedrela odorata L. IN THE NEOTROPICAL REGION - Coelho, Thassiana Lacerda; Magnago, Luiz Fernando Silva; Mesquita, Ricardo Gabriel Almeida; Valle, Mara Lúcia Agostini (Floresta, 2024)
Understanding wood properties is crucial for optimizing its technological potential, enhancing both the effectiveness of use and product quality. Among these properties, density is regarded as one of the most significant. Numerous studies have documented the relationship between wood density and climate. However, the influence of climatic factors on the density variation of native species remains largely unexplored. Cedrela odorata L., a species traditionally logged in Brazil and widely distributed across the Neotropical region, requires further analysis to understand its potential response to varying climate patterns, thereby informing its management. This study aimed to determine the relationship between the basic density of Cedrela odorata L. and the climatic conditions in the Neotropical region. A comprehensive database was compiled from published scientific literature. Statistical analyses were conducted using Generalized Linear Models (GLM), with the best models selected based on the corrected Akaike Information Criterion (AICc). The presence of spatial patterns was assessed using Moran’s Index to verify spatial autocorrelation. The study identified significant relationships between the wood density of C. odorata and variables such as mean annual temperature and annual precipitation. The findings indicate a strong interaction between the climatic variables analyzed and the basic density of Cedrela odorata L. wood, with density being more sensitive to mean annual temperature.